Mothers' experiences of exclusive breastfeeding in a postdischarge home setting - Van Ryneveld, M; Mwangome, M; Kahindi, J; Jones, C (Wiley, 2020)
Re-establishment and maintenance of exclusive breastfeeding (EBF) is recommended by the World Health Organization for the nutritional rehabilitation of malnourished infants under 6 months; however, there is no explicit guidance on how this should be achieved. The IBAMI study—a pilot study conducted in Kilifi, Kenya—implemented these recommendations using an intervention for hospitalized infants and their mothers that included ward-based breastfeeding peer supporters. This paper explores how the challenges of maintaining EBF are recontextualized after infant hospitalization for malnutrition. Four weeks after discharge, semistructured interviews on experiences of trying to maintain EBF in a postdischarge home setting were conducted with a total of 20 mothers. Although most stated the aspiration of maintaining EBF for 6 months, a range of challenges were reported and not all had successfully maintained EBF post discharge. Reported challenges include the stress of household chores, food insecurity, technical difficulties and social stigma of expressing breast milk, pressure from neighbours and family members to introduce mixed feeding, and needing more community-based awareness and support. Most of these challenges were specific to the home setting and were not easily surmountable, despite the breastfeeding practices mothers had learned in the ward. Indeed, in some cases, challenges were exacerbated by the overmedicalized nature of the breastfeeding practices taught in the ward. In order to aid the transition from ward to home, there may be a need to further translate ward-based education and promotional messaging for EBF into a community setting, targeting other caregivers as well.